PTH-108 The outcome of transarterial chemoembolization for liver cancer patients in aberdeen royal infirmary. (8th June 2018) - Taj-aldeen, Wamedh; Kattiparambil, Sajith; Clegg, Fiona; Siu, Wilson; Raja, Amalraj; Saraswat, Lokesh; Straiton, Jack; Balasubramaniam, Vijayan; Fraser, Andrew; Mcleman, Lindsey; Mukhopadhya, Ashis
Abstract : Introduction: Hepatocellular carcinoma (HCC) is the 5th most common cancer worldwide, it often presents in advanced stages with limited treatment options, reflected in its poor prognosis. Transarterial chemoembolisation (TACE) is an established palliative treatment for patients with advanced HCC, but outcomes vary. In this retrospective observation study, we assessed radiological response and survival outcome following TACE in a single large centre. Methods: Data was collected between October 2013 and December 2017 for all TACE procedures at Aberdeen Royal infirmary by access to MDT records and radiological data. Basic demographics, aetiology and severity of underlying liver disease, lesion characteristics (number and size) and Barcelona staging (BCLC) were all recorded. Scans were reviewed by two consultant radiologists and modified RECIST criteria used to assess the radiological response (complete response: disappearance of all target lesions; partial response: minimum 30% decrease in sum of the longest diameter of target lesions). Results: 31 patients underwent TACE procedure (1 excluded due to loss of follow up). Mean age 68.5±7.33, 76.6% were male and 29/31 White British. All procedures used doxorubicin loaded beads. The main aetiologies were non-alcoholic fatty liver disease 11 (36%), Alcohol-related liver disease 10 (33.3%), hepatitis C virus 5 (16.6%). 86.7% had underlying liver cirrhosis. BCLC staging of patients was 12 (40%) A, 17 (56.6%) B, 1 (3.4%) C. 8 patients (26.6%) had TACE as a bridge for transplant or tumour resection. A CT scan 6 weeks post-procedure showed 7 patients (23.3%) complete response while 19 patients (63.3%) had partial response, only 4 patients (13%) had no response. Of the 11 patients with a single tumour lesion <5 cm, 8 (72.7%) had complete response and 3 (27.3%) partial response. During the median follow up time of 17 months (1–41), 8/30 patients had progression of the same liver lesion (33.3%) while 11 (36.3%) developed new liver lesions, and 5 (16.6%) distant metastasis. 11 (36.3%) patients died during the follow up period, 3 (27.3%) had a small initial tumour lesion. Mortality rates at BCLC stage A was 5/12 (41.6%) and B 5/17 (29.4%). Of the 8 using TACE as a bridge to curative treatment, 3 underwent liver transplant, 2 remain active on transplant list, 1 underwent surgical resection and 2 were removed from the list. There were no major complications noted post TACE procedures. Conclusions: TACE helps to improve the survival and downstage HCC to allow curative treatment options. Only a small number had no radiological response to TACE. Those with initial BCLC B appeared to have a better survival, likely due to smaller numbers in stage A group. Those with a single tumour lesion less than 5 cm showed the best radiological response rate and survival.